Pemberdayaan Ekonomi Masyarakat Melalui Gebyar Gerak Sukamulya di Desa Sukamulya Kabupaten Ciamis - Muiz, Aris Nurul; Aliffi, Lutfi Fathan; Mutolib, Abdul (Research and Social Study Institute (RESSI), 2023)
Thematic Real Work Lectures (KKN) are an intracurricular lecture activity in the form of community service with an interdisciplinary and cross-sectoral approach. Micro and Small Enterprises (MSEs) can be defined as a small-scale business unit that is simply managed by economic business actors. The challenge of MSEs in Sukamulya Village is that they have not yet developed due to a lack of awareness of the provision of facilities and support from several local institutions or organizations so that they have not been able to contribute to the village economy. The aim of this community service is to make efforts to empower MSEs through the Sukamulya Movement event and improve the economy for the people of Sukamulya Village. The method used in this paper is the community empowerment method by referring to the theory according to the Delivery Team. Community service activities were carried out by KKN-T Group 04 of Siliwangi University with the result of determining a strategic location, namely at the Sukamulya Village GOR, with 15 MSEs and 10 PKLs participating, as well as the high enthusiasm of the community of around 600 people spilling over so that the MSEs who were registered at This celebration gets a lot of profit from sales and it is hoped that this activity can continue to be carried out by the local government in Sukamulya Village.